How to make perpetrators in denial disclose more information about their crimes. Issue 6 (2nd July 2016) - Tekin, Serra; Granhag, Pär Anders; Strömwall, Leif A.; Vrij, Aldert
ABSTRACT: This study examined interview techniques for eliciting admissions from perpetrators of a crime. Two techniques derived from the Strategic Use of Evidence (SUE) framework (SUE-Confrontation and SUE-Confrontation/Explain) were compared to an Early Disclosure of Evidence technique. Participants ( N = 75) performed a mock criminal task divided into three phases before being interviewed. In the SUE conditions, statement-evidence inconsistencies were obtained by strategic interviewing for Phases 1 and 2. For both SUE conditions, the interviewer confronted the suspects with these inconsistencies, emphasising that withholding information undermined their credibility. For the SUE-Confrontation/Explain condition, the suspects were asked to explain each inconsistency. To restore their credibility, the suspects in the SUE conditions were expected to become more forthcoming in Phase 3 (the phase which lacked information). The suspects in the SUE-Confrontation condition (vs. the suspects in the Early Disclosure condition) disclosed more admissions about Phase 3. As predicted, the suspects in the SUE conditions perceived the interviewer to have had comparatively more information about Phase 3. The suspects in the SUE-Confrontation/Explain condition strived to maintain their credibility either by fitting their story to the evidence or by sticking to the initial story. The study shows that the SUE technique is effective for eliciting admissions.